2020
DOI: 10.1016/j.mrfmmm.2020.111693
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic opportunities for PLK1 inhibitors: Spotlight on BRCA1-deficiency and triple negative breast cancers

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 109 publications
0
16
0
Order By: Relevance
“…Thus, targeting those proteins is a promising approach in breast cancer medication. In breast cancer (BC) patients, a high expression level of PLK1 was noted as an essential marker for cancer progression and metastasis with a poor prognosis [37,38]. PLK1 involves in G2/M progression.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, targeting those proteins is a promising approach in breast cancer medication. In breast cancer (BC) patients, a high expression level of PLK1 was noted as an essential marker for cancer progression and metastasis with a poor prognosis [37,38]. PLK1 involves in G2/M progression.…”
Section: Discussionmentioning
confidence: 99%
“…PLK1 is a cell cycle kinase that participates in eukaryotes mitosis and can be used as a biomarker and potential therapeutic target in oncology. 33 It has been reported that overexpression of PLK1 can promote the progression of breast cancer, 33 renal cell carcinoma, 34 gastric cancer. 35 With regard to the study of PLK1 in OS, Zhu et al found that the proliferation of OS cells was inhibited with the intervention of PLK1 expression.…”
Section: Discussionmentioning
confidence: 99%
“…BUB1B, which blocks the activation of APC Cdc20 , is the central component of the mitotic checkpoint for spindle assembly, and it was proved overexpressed in breast cancer and acts as a oncogene (Koyuncu et al, 2020). PLK1, as a member of polo-like kinase family, is involved in mitotic entry, centrosome maturation, spindle assembly, and cytokinesis process (Golsteyn et al, 1995;García et al, 2020). Results from CRISPR-cas9 screening suggested that knocking out these genes leads to cell death in breast cancer of all subtypes, and inhibitors targeting these genes may be potential therapeutic strategies for breast cancer.…”
Section: Discussionmentioning
confidence: 99%